(untitled) (Revista Sistemas de Producción Agroecológicos, 2023)
Corneal ulcers are pathologies that affect the integrity of the cornea. Depending on the type of lesion, it may require surgical treatment, as in the case of deep corneal ulcers, since they go through the corneal epithelium. Generally, it is a pathology that is frequently presented in small animal veterinary clinics. For this reason, this work analyzes the different biological grafts used in the correction of corneal ulcers in canines, their components, their benefits, as well as the different preservation methods used for them. Emphasis is made on the amniotic membrane since this biomaterial presents different components that make it stand out from the others, which is reflected in the results of the treatment. In addition, it has more research contributions talking about these benefits, which justifies the recommendation of its use compared to other membranes used. As for the hemoderivatives, the benefits that each of them contain are mentioned, in addition to their action as an adjuvant in the treatment of deep corneal ulcers. Finally, the theory was evaluated in the report of a clinical case of descemetocele due to a deep ulcer in the left cornea, not perforated.